2020
DOI: 10.1111/jcmm.16203
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA in cardiovascular disease: Expression, mechanisms and clinical prospects

Abstract: Circular RNAs (circRNAs) are a group of covalently closed, endogenous, non‐coding RNAs, which exist widely in human tissues including the heart. Increasing evidence has shown that cardiac circRNAs play crucial regulatory roles in cardiovascular diseases (CVDs). In this review, we aimed to provide a systemic understanding of circRNAs with a special emphasis on the cardiovascular system. We have summarized the current research on the classification, biogenesis and properties of circRNAs as well as their particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…CircRNAs are abundant, endogenous, stable, conserved, and cell-type specific molecules, which could participate in regulating cell function ( Kristensen et al, 2019 ). Increasing attention has focused on functions for circRNAs in human diseases, such as neurological diseases (W. Han et al, 2018 ; Chen et al, 2020a ), cardiovascular disease ( Zhang et al, 2020a ; Tang et al, 2021 ), diabetes mellitus ( Zhang et al, 2020b ; Zaiou, 2020 ), and tumorigenesis ( Goodall and Wickramasinghe, 2021 ; G. ; Huang et al, 2020b ), especially cardiovascular diseases. For instance, Garikipati et al found that circRNAs were altered expressed in the mouse model of post myocardial infarction (MI) ( Garikipati et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are abundant, endogenous, stable, conserved, and cell-type specific molecules, which could participate in regulating cell function ( Kristensen et al, 2019 ). Increasing attention has focused on functions for circRNAs in human diseases, such as neurological diseases (W. Han et al, 2018 ; Chen et al, 2020a ), cardiovascular disease ( Zhang et al, 2020a ; Tang et al, 2021 ), diabetes mellitus ( Zhang et al, 2020b ; Zaiou, 2020 ), and tumorigenesis ( Goodall and Wickramasinghe, 2021 ; G. ; Huang et al, 2020b ), especially cardiovascular diseases. For instance, Garikipati et al found that circRNAs were altered expressed in the mouse model of post myocardial infarction (MI) ( Garikipati et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that circRNAs function as pivotal regulators in various physiological and pathological activities. Further, their circular conformation endows them with a unique ribonuclease-resistant character not possessed by their linear counterparts, making them ideal biomarkers and treatment targets (10).…”
Section: The Biogenesis Characteristics and Functions Of Circrnasmentioning
confidence: 99%
“…Circular ribonucleic acids (circRNAs), the newly discovered non-coding RNAs, have been the subject of extensive research in different types of diseases, such as lung cancers, neurological disorders, and cardiovascular diseases (8)(9)(10). Numerous studies have shown that circRNAs are pivotal regulators in bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…This abundant class of molecules is generated from a non-canonical splicing event, called backsplicing, which occurs through the formation of a covalent bond between a downstream splice-donor site and an upstream splice-acceptor site [39]. Along with the ease of purifying from peripheral fluids [68,69] and the high stability, the altered expression of circRNAs in both muscular [70] and cardiovascular pathologies [71] encouraged their use as non-invasive and quantifiable biomarkers. This application is expected to burst in the next few years to diagnose specific pathological states and monitor therapeutic outcomes.…”
Section: Chemical and Structural Properties Define Multiple Arrays Of Rna Functionsmentioning
confidence: 99%